Peran Psikologi Pendidikan dalam Pembelajaran Pendidikan Agama Islam di Madrasah - Hasanah, Amalia; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
Islamic Religious Education is an effort to guide students so that they can master and practice the teachings of Islam according to the guidance of sharia. To improve the quality of Islamic education learning, one way is to develop Islamic education learning materials with psychology. The role of psychology is to build spiritual and social attitudes in the learning process of Islamic Religious Education is needed because in accordance with the current curriculum, building spiritual and social attitudes aims to produce graduates who are productive, innovative and affective or have character, through strengthening attitudes, skills and knowledge in an integrative manner. This research uses a qualitative research method with a literature model. Researchers documented and analyzed literature on the role of educational psychology in learning Islamic Religious Education (PAI) in madrasah from primary and secondary sources. The results of this study indicate that a teacher must study the science of educational psychology fundamentally with the intention of gaining knowledge about various aspects as the main foundation, especially developing Islamic education learning materials.